Comparison of the Effectiveness of Resilience Training and Cognitive Emotion Regulation Training on Social Interaction and Theory of Mind in Children with Sluggish Cognitive Tempo - Sattarian , Rafat; Aghdasi, Ali Naghi; Aghapour, Mehdi; Moheb , Naimeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The aim of this study was to compare the effectiveness of resilience training and cognitive emotion regulation training on social interaction and theory of mind in children with sluggish cognitive tempo. Methodology: The research method was quasi-experimental with a pre-test, post-test, and follow-up design, including a control group. The statistical population consisted of all 9- to 12-year-old male elementary school students with sluggish cognitive tempo in Tabriz in 2023. A total of 45 participants were selected from the statistical population using purposive sampling and were randomly assigned to experimental and control groups. The first experimental group received resilience training in 10 sessions of 45 minutes over four weeks, while the second experimental group underwent cognitive emotion regulation training in 10 sessions of 45 minutes over four weeks. The control group did not receive any intervention. The research instruments included the Sluggish Cognitive Tempo Questionnaire, the Social Skills Rating Scale, and the Theory of Mind Questionnaire. Data were analyzed using repeated measures analysis of variance. Findings: The results indicated that both resilience training and cognitive emotion regulation training had significant effects on social interaction and theory of mind in children with sluggish cognitive tempo (p < .05). Additionally, post hoc test results revealed no significant difference between the two therapeutic approaches in terms of social interaction and theory of mind (p > .05). Conclusion: This study found that both resilience training and cognitive emotion regulation training effectively improved social interaction and theory of mind in children with sluggish cognitive tempo, with no significant difference in their effectiveness.